2019
DOI: 10.1002/ecs2.2643
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from urban ponds are driven by nutrient status and hydrology

Abstract: Inland waters emit significant quantities of greenhouse gases (GHGs) such as methane (CH4) and carbon dioxide (CO2) to the atmosphere. On a global scale, these emissions are large enough that their contribution to climate change is now recognized by the Intergovernmental Panel on Climate Change. Much of the past focus on GHG emissions from inland waters has focused on lakes, reservoirs, and rivers, and the role of small, artificial waterbodies such as ponds has been overlooked. To investigate the spatial varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 60 publications
10
40
1
Order By: Relevance
“…The positive association between NOx and CO2 found in our reservoirs is consistent with similar patterns seen with dissolved inorganic N species in other artificial waterbodies (Ollivier et al, 2019;Peacock et al, 2019) and regional prairie lakes (Wiik et al, 2018). In some lakes, high N loading favoured elevated heterotrophy, despite simultaneous boosts in primary production which draws down free CO2 (Huttunen et al, 2003;Cole et al, 2000).…”
Section: Environmental Drivers Of Co2 Concentrationssupporting
confidence: 89%
“…The positive association between NOx and CO2 found in our reservoirs is consistent with similar patterns seen with dissolved inorganic N species in other artificial waterbodies (Ollivier et al, 2019;Peacock et al, 2019) and regional prairie lakes (Wiik et al, 2018). In some lakes, high N loading favoured elevated heterotrophy, despite simultaneous boosts in primary production which draws down free CO2 (Huttunen et al, 2003;Cole et al, 2000).…”
Section: Environmental Drivers Of Co2 Concentrationssupporting
confidence: 89%
“…In particular, CH 4 concentrations were lowest when WRT was long (> 1 year) and water was derived mainly from snow or groundwater sources (δ 18 O depleted). This may be due to a combination of reasons, including the prevalence of sulfate delivered from groundwater (Pennock et al, 2010), dilution of waterbody from snowmelt inflow, and sediments depleted in labile carbon due to longer biogeochemical processing times in the dams. The potential effect of sulfate limiting methanogenesis is in agreement with the strong negative relationship found between CH 4 and conductivity in our model (Fig.…”
Section: Environmental Drivers Of Ch 4 Concentrationsmentioning
confidence: 99%
“…This study builds on from our previous farm reservoir GHG research which found an unexpected nitrous oxide (N 2 O) sink in 67 % of reservoirs . The hydroclimate, lithology and edaphic features are vastly different compared to previous studies of agricultural areas (Australia, India, USA), with factors that favour CO 2 uptake by alkaline surface waters (Finlay et al, 2009(Finlay et al, , 2015 and lead to high variability in CH 4 fluxes from regional wetlands (Pennock et al, 2010;Badiou et al, 2019). Our aim was to identify the key environmental conditions regulating CO 2 and CH 4 fluxes, as well as to evaluate these baseline data in the context of emission mitigation strategies.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Holgerson and Raymond () estimate that natural ponds contribute 40% of diffusive CH 4 emissions from lentic inland waters worldwide. Ponds created on the terrestrial landscape for a variety of purposes including stock watering, irrigation, and aquaculture have been also found to emit CH 4 (Ollivier et al, ; Peacock et al, ). In some cases, these ponds emit CH 4 at higher rates than natural ponds through diffusive and ebullition flux pathways (Grinham et al, ), though more comparative data are needed.…”
Section: Introductionmentioning
confidence: 99%